2009
DOI: 10.1021/ol900533h
|View full text |Cite
|
Sign up to set email alerts
|

Optically Active Dinuclear Palladium Complexes Containing a Pd−Pd Bond: Preparation and Enantioinduction Ability in Asymmetric Ring-Opening Reactions

Abstract: Optically active dinuclear palladium complexes containing a Pd-Pd bond were prepared by using (R,R)-bis(tert-butylmethylphosphino)methane ((R,R)-t-Bu-MiniPHOS). The dinuclear palladium complexes coupled with silver triflate exhibited good to excellent enantioselectivities up to 99% in palladium-catalyzed alkylative ring-opening reactions of azabenzonorbornadienes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
18
0

Year Published

2010
2010
2018
2018

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 66 publications
(18 citation statements)
references
References 40 publications
0
18
0
Order By: Relevance
“…Although the alkylative ARO of oxa/azabicylic alkenes has been demonstrated with hard organometallic reagents,4 the enantioselective alkylative ring opening of oxabicyclo‐[2.2.1]heptanes and azabicyclic alkenes has only been achieved with the use of dimethyl‐ and diethylzinc 2a,b,f. 3c,d In general, the alkylative ARO has been limited in scope due to the instability and lack of accessibility of the organometallic reagents. Consequently, only simple alkyl fragments that lack functional group handles have been reported.…”
Section: Methodsmentioning
confidence: 99%
“…Although the alkylative ARO of oxa/azabicylic alkenes has been demonstrated with hard organometallic reagents,4 the enantioselective alkylative ring opening of oxabicyclo‐[2.2.1]heptanes and azabicyclic alkenes has only been achieved with the use of dimethyl‐ and diethylzinc 2a,b,f. 3c,d In general, the alkylative ARO has been limited in scope due to the instability and lack of accessibility of the organometallic reagents. Consequently, only simple alkyl fragments that lack functional group handles have been reported.…”
Section: Methodsmentioning
confidence: 99%
“…Many reports of catalytic processes mediated by dinuclear palladium(I) complexes used as catalyst precursors have been published. Notably, almost all of these studies reported remarkably high efficiencies for the catalytic reactions, which included Suzuki–Miyaura coupling [ 28 ], Sonogashira coupling [ 57 ], Hiyama coupling [ 29 ], Buchwald–Hartwig amination [ 26 ], Kumada–Corriu and Negishi coupling [ 58 ] ( Scheme 1 ), and others [ 59 , 60 , 61 ], suggesting that dinuclear Pd(I) complexes can generate species with unusually high activity as key intermediates. However, in all but a few examples, it was unclear how these reactions proceeded from the dinuclear Pd(I) complexes.…”
Section: Catalytic Applicationsmentioning
confidence: 99%
“…Unlike gold, palladium has enjoyed a compelling reputation as a chemically active material. In fact, many palladium compounds including palladium complexes are currently being utilized as catalysts in asymmetric syntheses, [40,41] cross coupling, [42][43][44][45][46] and alkylation reactions. [47,48] Additionally, palladium is known for its uniquely high hydrogen gas absorption capacity, which has been documented to occur even at room temperature and pressure.…”
Section: Introductionmentioning
confidence: 99%